Two new species of Seira Lubbock, 1870 (Collembola: Entomobryidae: Seirinae) from Brazilian Caatinga - Nunes, Rudy Camilo; Cipola, Nikolas Gioia; Bellini, Bruno Cavalcante (Zootaxa, 2021)
Two new species of Seira Lubbock are described and illustrated, Seira picoensis sp. nov., from Picos municipality, and Seira trisetosa sp. nov., from Serra das Confusões National Park, Caracol municipality, both in Piauí State, Brazil. Seira picoensis sp. nov. resembles other species of the genus with four macrochaetae in abdomen I, but differs by other aspects of the dorsal chaetotaxy and unguiculus shape. Seira trisetosa sp. nov. resembles S. ferruginea Rapoport & Izarra, S. frater (Bonet), S. oceanica Yosii and S. tinguira Cipola & Bellini by the abdomen I with 3 macrochaetae, but also differs by other features such as the antenna IV morphology, overall dorsal chaetotaxy and unguiculus shape. We also provide a brief discussion on the mucro shape in Seirinae.